Penerapan Metode Profile Matching untuk Menentukan Program Pemberdayaan Masyarakat pada Desa S1 Jati Baru - Perwira, Yuda; Apriani, Wira; Nuraisana, Nuraisana; Affandi, Egi; Daulay, Suandi (Jurnal Informatika Ekonomi Bisnis, 2024)
This research aims to test the effectiveness of applying the Profile Matching method in determining community empowerment programs in Desa S1 Jati Baru. Desa S1 Jati Baru, a village in the Pagar Merbau sub-district of Deli Serdang Regency, North Sumatra Province, faces several development challenges. In this context, this research considers the Profile Matching method as a potential approach to formulate more relevant and sustainable empowerment programs. The study employs a qualitative approach involving in-depth interviews and focus group discussions with various stakeholders in Desa S1 Jati Baru. The collected data is then analyzed using content analysis methods to identify the community's needs, aspirations, and potential. The research findings indicate that the Profile Matching method provides a deeper understanding of the needs and aspirations of the Desa S1 Jati Baru community. Based on the generated profile, various empowerment programs that better match the community's characteristics and needs were identified, with the development of agricultural MSMEs emerging as the best option with the highest total score of 2.36. This program received high scores on core factors, indicating that it is highly suitable for the community's educational background, with most residents being vocational high school graduates, and has great potential to increase the village's income.